Dampak Penyalahgunaan Narkoba DiTinjau Dari Segi Hukum, Miras Di Tinjau Dari Segi Agama Dan Kesehatan Di Desa Jono Kab. Sigi Provinsi Sulawesi Tengah: The Impact of Drug Abuse Reviewed from a Legal Perspective, Alcoholic Beverages Reviewed from a Religious and Health Perspective in Jono Village, Sigi Regency, Central Sulawesi Province - Maryam; Imam Hikam; Muhammad Asrum (Jurnal Kolaboratif Sains, 2025)
The tri dharma of higher education is the obligation of lecturers, and one of them is community service. This service raised the theme of health education about the impact of drug use in terms of law, Miras in terms of religion and health. Previously, a joint observation was made by the Sheep Indonesia Foundation that the problem obtained in Jono Village was the average community consuming liquor (Miras). Jono Village is a remote area in Sigi Regency. The purpose of this community service is to increase public knowledge about the impact of the Miras. The method of implementing community service with direct counseling techniques to the community with Flip chart and Leaflet media. The results of community service are very enthusiastic to listen to the material. Previously, many residents did not know the impact of liquor. This is reflected in the number of questions asked regarding the harm caused by drinking liquor. In the evaluation session, the community is given questions and the average community can answer correctly according to the material provided. Conclusions community service activities have been carried out well and lancer. The community welcome is very good and it is hoped that the community can avoid liquor, and this activity and community service can be carried out regularly.